The synergistic role of high‐fat diet and genetic predisposition in Alzheimer's disease. (December 2021) - Oblak, Adrian L; Kotredes, Kevin P; Reagan, Alaina M; Pandey, Ravi S; Sasner, Michael; Carter, Gregory W; Lamb, Bruce T.; Howell, Gareth R
Abstract: Background: Age, genetic variants, and environmental factors such as consumption of a high fat diet contribute to Alzheimer's disease (AD) risk. Diets high in fat also increase disease neuropathology and/or cognitive deficits in mouse models relevant to AD. However, the effect of a high‐fat diet on biometrics, neuropathology and cognitive impairments in novel models of late‐onset AD (LOAD) is unknown. To date, in the IU/JAX/PITT MODEL‐AD Center, we have focused on developing mouse models containing combinations of genetic risk variants in genes including APOE, Trem2, Mthfr and Plcg2 . In addition, we have humanized the mouse Aβ peptide that is reported to be more amyloidogenic than the mouse Aβ peptide. Here, we now test the effect of incorporating a high fat diet as an environmental risk factor to improve the alignment of mouse models to LOAD. Methods: A high fat diet (45% high fat/high sugar, HFD) was provided to mice from two to 12 months of age from four LOAD‐relevant models on a C57BL/6J genetic background (B6); B6. APOE E4 TREM2 R47H (B6. LOAD1 ), B6. APOE E4 TREM2 R47H hAβKI (B6. LOAD2 ), B6. LOAD1.Mthfr C677T and B6. LOAD1.Plcg2 M28L . Control mice from each strain were fed standard chow diet as a control (6% fat). Metabolic assays, including weight and blood glucose, and frailty index score were performed throughout the study. Cholesterol, liver enzymes, transcriptomics and AD‐relevant neuropathology was performed at terminal timepoints. Results: Consumption of a HFD exacerbated age‐related increases in frailty and body weight in B6.LOAD2 and B6.LOAD1. Plcg2 M28L, B6. LOAD1.Mthfr C677T mice compared to control diet. A HFD increased glucose, cholesterol, triglycerides and liver enzymes in all strains compared to control diet. Importantly, transcriptomic analysis of brain samples using the Nanostring AD panel revealed that the presence of the Plcg2 M28L risk variant in combination with HFD caused an elevation of human AD‐relevant inflammatory genes that didn't occur in other strains on HFD or in B6.LOAD1. Plcg2 M28L mice on control diet. Conclusions: This study aims to clarify the synergistic role of genetics, age and high fat diet in the progression of AD‐related pathology in novel mouse models of LOAD. These findings provide a platform to combine LOAD variants with environmental influences, providing more relevant models for preclinical efficacy studies.